Grammatical emphasis means in English with reference to their Vietnamese equivalents. / Phạm Thị Kim Dung; NHDKH Assoc.Prof.Dr Hoang Tuyet Minh - Phạm, Thị Kim Dung
The study is aimed at grammatical emphasis means in English with reference to their Vietnamese equivalents by using descriptive method and comparative analysis as the major method. The research is done to investigate the features of grammatical emphasis means in English, finding out the similarities and the differences between grammatical emphasis means in English with reference to their Vietnamese equivalents in order to help learners of English to learn English effectively. In doing the research, descriptive method and comparative analysis are done either to describe the meanings conveyed by the grammatical emphasis structures/ means to determine the similarities between grammatical emphasis means in English and in Vietnamese. Data for this study were collected from two foreign novels, namely, Wuthering Heights by Emily Brontë, Harry Potter and the Half-Blood Prince by J. K. Rowling and some Vietnamese novels such as, Dế mèn phiêu lưu ký, written by Tô Hoài, Hà Nội trong mắt tôi by Nguyễn Khải and Truyện ngắn tuyển chọn, written by Nam Cao. This study has been primarily carried out to answer two questions, one is to investigate the possible meanings of grammatical emphasis means in English and the other is to investigate their Vietnamese equivalents. The results provide some supports for learners to have a deep understanding in learning English grammar.